2021
DOI: 10.1038/s41598-021-01302-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of the gene expression profile in muscle atrophy after spinal cord injury

Abstract: Spinal cord injury (SCI) is often accompanied by muscle atrophy; however, its underlying mechanisms remain unclear. Here, the molecular mechanisms of muscle atrophy following SCI were investigated. The GSE45550 gene expression profile of control (before SCI) and experimental (14 days following SCI) groups, consisting of Sprague–Dawley rat soleus muscle (n = 6 per group), was downloaded from the Gene Expression Omnibus database, and then differentially expressed gene (DEG) identification and Gene Ontology, path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Muscle atrophy is an important manifestation of sarcopenia. Previous studies have shown that pathway changes related to protein ubiquitination and energy production are common features during muscle atrophy (20). In addition, recent studies have also shown that mitochondrial dysfunction (21), inflammatory pathways (22), and drug toxicity are also closely related to the occurrence of muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle atrophy is an important manifestation of sarcopenia. Previous studies have shown that pathway changes related to protein ubiquitination and energy production are common features during muscle atrophy (20). In addition, recent studies have also shown that mitochondrial dysfunction (21), inflammatory pathways (22), and drug toxicity are also closely related to the occurrence of muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enriched 30 signaling pathways, among which the important signaling pathways included the citrate cycle (TCA cycle), ascorbate and aldarate metabolism, drug metabolism, TGF-beta signaling pathway, tyrosine metabolism, sphingolipid metabolism, fatty acid degradation, pyruvate metabolism, TNF signaling pathway, relaxin signaling pathway, and fluid shear stress and atherosclerosis. The citrate cycle (TCA cycle), pyruvate metabolism, and fatty acid degradation have also been predicted to be important signaling pathways in muscle atrophy in spinal cord injury ( Huang et al, 2021 ). The TGF-beta signaling pathway has been previously reported to play an important regulatory role in muscle atrophy ( Yoshihara et al, 2022 ) and is an important signaling pathway in the regulation of muscle atrophy ( Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the identi cation of differentially expressed genes (DEGs), we performed signi cance analysis of microarrays (SAM) to screen for genes in the previously designated groups showing signi cantly differential expression [7]. Differences with a q value < 0.05 and a fold change > 2.0 or < − 2.0 were considered statistically signi cant.…”
Section: Differentially Expressed Gene Analysismentioning
confidence: 99%